KINETICS AND THERMODYNAMIC STUDIES ON SORPTION POTENTIAL OF HYBRID ADSORBENT PRODUCED FROM SNAIL SHELL AND RICE HUSK - Igbonekwu, L. I.; Ajemba R.O.; Ugonabo V. I. (International Journal of Innovations in Engineering Research and Technology, 2022)
The present study deals with the application of Snail Shell and Rice Husk (RH-SS), an agricultural and animal waste, for the adsorptive removal of phenol from pharmaceutical effluent. This paper incorporates the effects of time, dose, temperature, concentration, and pH on the efficient removal of phenol from pharmaceutical Effluent. Batch kinetic and isotherm studies have also been performed to understand the ability of the adsorbents. The adsorption behavior of the Phenol has been studied using Freundlich and Langmuir adsorption isotherm models. The monolayer adsorption capacity determined from the Langmuir adsorption equation has been found as 149.25 mg/g. Kinetic measurements suggest the involvement of pseudo-second-order kinetics in adsorptions. Adsorption of phenol on adsorbents was found to increase on decreasing phenol effluent concentration, increasing pH up to 5 and increasing effluent temperature up to 35oC. Overall, the present findings suggest that the composite of Rice Husk and Snail Shell (RH-SS) is environmentally friendly, efficient and low-cost biosorbent which is useful for the removal of Phenol from waste water.